SMEs in a Digital Era: The Role of Management - Irena Mladenova (Administrative Sciences)
This article aims to explore the role of management in translating the external factors’ and internal barriers’ impacts on the level of adoption of digital technologies as a lever for change in business operations and processes in small- and medium-sized enterprises (SMEs). SMEs face a distinct set of challenges when adopting digital technologies, often lacking resources and knowledge. On the other hand, they have certain characteristics, such as simpler organisational structures and processes, that make them more flexible than larger firms in leveraging technologies into new business models. Data for this study are obtained from 989 SMEs in Bulgaria in the manufacturing and services sectors. A PLS–SEM analysis confirms eight hypotheses raised on the relationships between environmental factors and government support and internal factors (management support, organisational flexibility, and risk-tolerant culture) that impact digital business intensity. Environmental factors’ impact is stronger than government support, while internal barriers are found to have no statistically significant relationship. The research findings highlight the important role of management support in guiding digital transformation through supporting organisational flexibility and promoting a risk-tolerant culture.